ChemInform Abstract: [2.2]Paracyclophane‐Derived Monodentate Phosphoramidite Ligands for Copper‐Catalyzed Asymmetric Conjugate Addition of Diethylzinc to Substituted Chalcones. Issue 35 (September 2015) - Han, Lei; Lei, Yang; Xing, Ping; Zhao, Xiao‐Long; Jiang, Biao
Abstract Copper‐catalyzed asymmetric conjugate addition of diethylzinc to chalcones is realized by using a newly synthesized [2.2]paracyclophane‐derived monodentate phosphoramidite ligand.